Is it export- or import-led growth? The case of Kenya - Peter Simiyu Wamalwa; Maureen Were (Journal of African Trade, 2021)
The role of exports in promoting economic growth has been widely acknowledged. This paper analyses the link between exports, imports, and growth performance in Kenya using time series data. Despite trade liberalization and export promotion policies pursued over time, Kenya's export growth has been sluggish, and exports are still strongly geared towards primary agricultural goods. Furthermore, empirical results show that aggregate exports have no statistically significant effect on output growth; instead, output growth is influenced by imports. Moreover, the diversification of imports has a larger impact on output growth than export diversification. Although analysis using disaggregated data shows a positive impact of machinery exports on output growth, the impact is smaller than that of imported manufactured and agricultural commodities. Therefore, the results generally suggest import-led growth and not export-led growth, signifying the economy's dependence on imports. There is a need for Kenya to revamp the export-led growth strategy by enhancing export competitiveness, increasing value-addition, export diversification, and leveraging on regional and global value chains.
Keywords: 330; Trade; export-led growth; import; import substitution; Kenya